Efeito de diferentes condições de maturação nas características do Queijo Minas artesanal - Pereira, Daniel Arantes (2019)
The production of artisanal cheese has recognized historical, social, cultural, and economic importance. The ripening process of artisanal cheeses ensures that conditions for microbiological, biochemical, and chemical changes occur so that the cheeses develop characteristic flavor, aroma, and texture. This process has been conducted under environmental conditions without humidity and temperature control with wide seasonal variation, giving non-standardization to the production. Producers have shown increased interest in controlling ripening conditions. However, it is unclear how changes in ripening conditions may affect the characteristics of artisanal cheeses and their safety. This research was conducted to evaluate the effect of ripening temperature and humidity on the characteristics of Artisanal Minas Cheese from Campo das Vertentes. We used a completely randomized experimental in a factorial scheme of 2 2 composed of two levels of humidity (80 and 95%) and two temperature values (12 and 18°C). We also evaluated the ripening under environmental (uncontrolled) condition in a total of five assays with three replicates. Under these conditions, we evaluated cheeses at 07, 14, 21, 42, and 60 days. Furthermore, we evaluated water activity, pH, humidity, fat in the dry extract, salt content in humidity, total protein, fixed mineral residue, texture profile, colorimetry (L*a*b*), and coliform enumeration at 35°C, E. coli, coagulase-positive Staphylococcus, lactic acid bacteria, and mold and yeast. The environmental humidity presented a significant effect on the water activity of 60-day-old cheeses. The differences in water activity related to ripening conditions occurred from 21 days. The cheeses ripened at 95% humidity showed the highest pH increase. The cheeses are classified as “low humidity” from 42 days of ripening. Cheeses ripened at 95% humidity presented the highest humidity at 60 days. The salt moisture content of cheese at 60 days was influenced by moisture and ripening temperature. The fixed mineral residue, fat content in the dry extract, total protein, and proteolysis depth were not affected by the ripening conditions. The proteolysis extension index was affected by humidity and temperature at 60 days. The composition of the luminosity of the rind and the interior of the cheeses changed between treatments at 42 days. We observed a tendency to decrease in the brightness of the shell. The cheese rind and interior chromatic coordinate a* showed an increasing tendency during ripening, while the rind´s chromatic coordinate b* did not differ between treatments and ripening time. Meanwhile, the interior of the cheeses showed differences regarding ripening times. Firmness affected the interaction between humidity and ripening temperature in 60-day-old cheeses. The cohesiveness presented significant differences regarding ripening conditions evaluated at the 42 and 60 days. The humidity and ripening temperature had no effect on elasticity, gummosity, and chewability. The ripening conditions did not influence the groups of microorganisms analyzed. All treatments showed a reduction in the counts of all microorganisms with ripening. The coliform count of all cheeses fell within the legal limits. The count of Staphylococcus aureus was according to the legislation in force at 60 days of ripening. However, in previous periods, the counts were higher than the recognized limits for toxin production. Lactic bacteria were the dominant cheese microbiota at 14, 21, and 60 days, while filamentous fungi and yeast, Staphylococcus aureus, coliforms at 30°C, and Escherichia coli were subdominant.